High aspect ratio metamaterials for enhanced tunability and sensitivity - Chiam, S.-Y. (2014)
2009 Conference on Lasers and Electro-Optics and 2009 Conference on Quantum Electronics and Laser Science Conference, CLEO/QELS 2009